Pore characteristics of pervious concrete and their influence on permeability attributes. (11th April 2022) - Shan, Jingsong; Zhang, Yuan; Wu, Shuyin; Lin, Zhansheng; Li, Lei; Wu, Qiulin
Highlights: 3D pore model of pervious concrete was established. Single-phase seepage test and simulation were conducted. Tortuosity and fractal dimension were introduced to pervious concrete. Pore throat size and coordination number of pores were analyzed. Abstract: The pore characteristics play a dominant role in the permeability attributes of pervious concrete. To study the relationship between the pore characteristics and permeability attributes of pervious cement concrete, the three-dimensional pore model based on CT (Computed tomography) technology and AVIZO software was established, and single-phase seepage test and simulation were conducted. The pore features of the pervious concrete were identified, and the spatial structure of the pores was analyzed. The results show that the fractal dimension and porosity are linearly related to each other. With the increase of the porosity, the tortuosity of the pervious concrete decreases. The number of pores and the maximum pore size also increase with an increase in the porosity. The internal pore size is basically within 0 ∼ 2000 mm 3 . The pore throat size follows a normal distribution. With the increase of porosity, the connectivity between the pores is improved and the coordination number of the pores increases. The simulation results show that the increase of the porosity, the decrease of the tortuosity, and the increase of the seepage channels result in an increase of permeability. The permeability simulation results are basically consistent with the indoor test results.